Study of secret sharing schemes based on quantum theory - ZHU Zhen-chao 1; ZHANG Yu-qing2 (Tongxin xuebao)
Quantum secret sharing（QSS） which is based on the laws of quantum mechanics,instead of mathematical assumptions can share the information unconditionally securely, according to the form of sharing information, quantum secret sharing can be divided into QSS of classical messages and QSS of quantum information,QSS of classical messages can be divided into QSS of classical messages based on entanglement and QSS of classical messages without entanglement, the representative protocols in three main branches of the quantum secret sharing schemes and its latest development were introduced, also prospect analysis of the schemes’ future development was given.